Un-frog-gettable riddles - Bernstein, Joanne E.; Wallner, Alexandra; Cohen, Paul, 1945- (Chicago : Whitman, 1981)
A collection of frog riddles which provide answers to questions such as "What side dish does Frog usually enjoy?" and "What does Frog drink with his favorite foods?"
6 11 13
Keywords: Riddles, Juvenile; Frogs -- Humor; Riddles; Frogs -- Wit and humor